2019
DOI: 10.3390/app9051035
|View full text |Cite
|
Sign up to set email alerts
|

PRGF-Modified Collagen Membranes for Guided Bone Regeneration: Spectroscopic, Microscopic and Nano-Mechanical Investigations

Abstract: The aim of our study was to evaluate the properties of different commercially available resorbable collagen membranes for guided bone regeneration, upon addition of plasma rich in growth factors (PRGF). The structural and morphological details, mechanical properties, and enzymatic degradation were investigated in a new approach, providing clinicians with new data in order to help them in a successful comparison and better selection of membranes with respect to their placement and working condition. Particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…In order to obtain accurate results, each nanoindentation test was repeated 16 times, while the optical image of the sample using a microscope allowed precise control between the sample position and the indenter. Young modulus values were obtained from load-displacement curves, by fitting parameters, using the Oliver-Pharr method [31,32].…”
Section: Structural Characterization Of Pva/ha/se-tio 2 Compositesmentioning
confidence: 99%
“…In order to obtain accurate results, each nanoindentation test was repeated 16 times, while the optical image of the sample using a microscope allowed precise control between the sample position and the indenter. Young modulus values were obtained from load-displacement curves, by fitting parameters, using the Oliver-Pharr method [31,32].…”
Section: Structural Characterization Of Pva/ha/se-tio 2 Compositesmentioning
confidence: 99%
“…They concluded that the changes in Young modulus values are correlated with the ultrastructural properties of each membrane type, more precisely the porosity; the higher the porosity, the lower the Young modulus value was obtained. After the PRGF treatment, the nanoindentation measurements indicated the Young modulus value ranging in the interval 2.8 -4 GPa, depending on the type of the membrane [8]. One can observe that antibacterial effect depends on the nanoparticles concentration in collagen film, for both bacteria investigated.…”
Section: Resultsmentioning
confidence: 92%
“…In the same time, they demonstrated that Young's modulus of collagen/chitosan films with different ratio was much higher than Young's modulus for collagen films or chitosan films unmodified. Ratiu et al [8] investigated the modifications of resorbable collagen membranes for guided bone regeneration, upon addition of plasma rich in growth factors (PRGF). They concluded that the changes in Young modulus values are correlated with the ultrastructural properties of each membrane type, more precisely the porosity; the higher the porosity, the lower the Young modulus value was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that platelets play a crucial role in hemostasis and healing processes. Several studies reported that, due to concentrated platelets, the use of autologous plasma rich in growth factors (PRGF) promotes the regeneration of bone and soft tissues, thus improving the therapeutic outcome [ 9 , 10 ]. The activated platelets release a wide variety of biologically active molecules, such as: vascular endothelial growth factor (VEGF), and platelet-derived growth factor (PDGR), transforming growth factor-beta 1 (TGF- β 1), and insulin-like growth factor-1 (IGF-1), which stimulate the healing process.…”
Section: ⧉ Introductionmentioning
confidence: 99%